Tumor biology correlates with rates of breast-conserving surgery and pathologic complete response after neoadjuvant chemotherapy for breast cancer: findings from the ACOSOG Z1071 (Alliance) prospective multicenter clinical trial - Boughey, Judy C. (2014)
OBJECTIVE: To determine the impact of tumor biology on rates of breast-conserving surgery and pathologic complete response (pCR) after neoadjuvant chemotherapy. SUMMARY BACKGROUND DATA: The impact of tumor biology on the rate of breast-conserving surgery after neoadjuvant chemotherapy has not been well studied. METHODS: We used data from ACOSOG Z1071, a prospective, multicenter study assessing sentinel node surgery after neoadjuvant chemotherapy in patients presenting with node-positive breast cancer from 2009 through 2011, to determine rates of breast-conserving surgery and pCR after chemotherapy by approximated biologic subtype. RESULTS: Of the 756 patients enrolled on Z1071, 694 had findings available from pathologic review of breast and axillary specimens from surgery after chemotherapy. Approximated subtype was triple-negative in 170 (24.5%) patients, HER2-positive in 207 (29.8%), and hormone-receptor-positive, HER2-negative in 317 (45.7%). Patient age and clinical tumor and nodal stage at presentation did not differ across subtypes. Rates of breast-conserving surgery were significantly higher in patients with triple-negative (46.8%) and HER2-positive tumors (43.0%) than in those with hormone-receptor-positive, HER2-negative tumors (34.5%) (P = 0.019). Rates of pCR in both the breast and axilla were 38.2% in triple-negative, 45.4% in HER2-positive, and 11.4% in hormone-receptor-positive, HER2-negative disease (P < 0.0001). Rates of pCR in the breast only and the axilla only exhibited similar differences across tumor subtypes. CONCLUSIONS: Patients with triple-negative and HER2-positive breast cancers have the highest rates of breast-conserving surgery and pCR after neoadjuvant chemotherapy. Patients with these subtypes are most likely to be candidates for less invasive surgical approaches after chemotherapy.